Dampak Keterbatasan LCD Proyektor terhadap Efektivitas Pembelajaran di Laboratorium Matematika - Zahro, Fatmatuz (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the impact of limited LCD projectors on the effectiveness of learning in the Mathematics Laboratory at Universitas Islam Negeri Maulana Malik Ibrahim Malang. The research employed a descriptive quantitative method involving 67 students as respondents through questionnaires and interviews. The findings indicate that the availability of LCD projectors is still limited, with many devices in suboptimal condition, and some laboratories lacking them entirely. This limitation affects the effectiveness of learning, particularly in delivering visual materials, facilitating communication between lecturers and students, increasing learning motivation, and supporting practical class outcomes. Survey data show that more than 90% of students agree that the presence of functional LCD projectors significantly improves comprehension and learning quality. Therefore, equitable provision and sustainable maintenance of LCD projectors are urgently required to enhance the quality of teaching and learning processes.